1998
DOI: 10.1016/s0022-2275(20)33300-9
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a phospholipid stabilized emulsion interface by bile salt: effect on pancreatic lipase activity

Abstract: Lipase is activated by binding to an insoluble emulsified or aggregated substrate. The extent of binding is related to the physicochemical as well as the compositional structure of the interface, the quality of the interface. 'Quality' is as yet undefined but thought to contain contributions from electrostatic interactions, orientation of substrate, and hydration forces. To investigate the electrostatic and compositional factors we have used olive oil-in-water emulsions prepared with phosphatidylcholine and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(62 citation statements)
references
References 22 publications
3
59
0
Order By: Relevance
“…Zero order kinetics are applied for lipolysis process. Therefore, enzyme binding increases with the increased product concentration due to the alteration of emulsion interface (Wickham et al, 1998). Incremental FFA release could be explained by increased lipase dispersion between the aqueous phase and the emulsion interface as lipase was activated when binding to an insoluble emulsified substrate.…”
Section: In Vitro Simulated Digestion Of Nanoemulsionsmentioning
confidence: 99%
“…Zero order kinetics are applied for lipolysis process. Therefore, enzyme binding increases with the increased product concentration due to the alteration of emulsion interface (Wickham et al, 1998). Incremental FFA release could be explained by increased lipase dispersion between the aqueous phase and the emulsion interface as lipase was activated when binding to an insoluble emulsified substrate.…”
Section: In Vitro Simulated Digestion Of Nanoemulsionsmentioning
confidence: 99%
“…The situation is greatly complicated, of course, by the various additional interactions with saliva, gastric juices, etc., and by various kinds of interfacial complexation and competition at the oil-water interface involving small-molecule surfactants, either present in the original food or released during digestion (phospholipids, bile salts, etc.). 123,124 Despite this complexity, it is reasonable to anticipate that the key principles already established in model biopolymer studies in vitro will have applicability under the physiological conditions existing when real food colloids are eaten and digested.…”
Section: Concluding Remarks and Future Trendsmentioning
confidence: 99%
“…7 Bile salts (BS) help to stabilize the emulsion droplets and modify the oil/ water interface for the adsorption of the lipase-colipase complex. 13 It has been reported that the lipolysis rate of triglycerides increases with BS concentration. 14 BS concentration in the gall bladder is between 10 and 50 mmol l À1 , in the intestine around 4-20 mmol l À1 , depending on the state (fasted or fed).…”
Section: Introductionmentioning
confidence: 98%